Experimental autoimmune encephalitis and inflammation in the absence of interleukin-12 - Burkhard Becher; Brigit G. Durell; Randolph J. Noelle (The Journal of Clinical Investigation, 2002)
IL-12 is considered a critical proinflammatory cytokine for autoimmune diseases such as multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE). IL-12 is a heterodimer composed of a p35 subunit and a common p40 subunit shared by other cytokines. Both IL-12 p40–/– and p35–/– mice fail to produce IL-12 p70 heterodimer. However, in contrast to p40–/– mice, p35–/– mice are highly susceptible to the induction of EAE, establishing that IL-12 p70 is not essential for the development of EAE. When compared with wild-type mice, both p40–/– and p35–/– mice show deficiencies in primary IFN-γ responses by lymph node cells. Expression profiling of the inflamed CNS revealed that Th2 cytokines such as IL-4 and IL-10 are upregulated in p35–/– mice, whereas LT-α and TNF-α levels are reduced. These studies show that a molecule other than IL-12 p70, which uses the p40 subunit, fulfills the functions previously attributed to IL-12 with regard to the development and pathogenesis of this autoimmune disease.